A new Steiner symmetrization defined by a subclass of analytic function in a complex domain - Alazman, Ibtehal; Ibrahim, Rabha W. (Frontiers in Applied Mathematics and Statistics, 2024)
In this effort, we present a new definition of the Steiner Symmetrization by using special analytic functions in a complex domain ( the open unit disk), with respect to the origin. This definition will be used to optimize the class of univalent analytic functions. Our method is based on the concept of differential subordination and the Carathèodory theory. Examples are illustrated in the sequel involving the modified Libera-Livingston-Bernardi integral operator over the open unit disk. The result gives that this integral satisfies the definition of bounded turning function (univalent analytic function).